Mineralogy and geochemistry of structurally-controlled metasomatic alteration of carbonate-rich manganese ore at Mamatwan Mine, Kalahari Manganese Field - Harawa, Esau Tonderai (Rhodes University, Faculty of Science, Department of Geology, 2017)
The Kalahari Manganese Field (KMF) located in the Northern Cape Province about 700km south west of Johannesburg contains 80% of the world manganese ore reserves. Mamatwan Mine is hosted within the low grade Mamatwan type ore and is located in the southernmost tip of the KMF. This mine is an open pit mine which is divided into three benches namely the top cut, middle cut and bottom cut. These three benches are structurally controlled by faults which influence the overall grade of the manganese ore. This study is a follow up work to the previous two studies carried out at Wessels Mine and Mamatwan Mine by (Gutzmer and Beukes) in 1995 and 1996 respectively with regards to alteration processes around fault controlled systems in which they concluded that epithermal fluids caused local reduction and bleaching of ore followed by oxidation and carbonate leaching of manganese ore through ascending oxidized groundwater. Metasomatic activity around fault controlled systems is controlled by three main processes namely redistribution, enrichment and depletion. These processes are determined by mobility/immobility of elements from the fault which are introduced into the pre-existing braunite carbonate rich ore. Elements such as Ca, Mg, Si, Fe, C and Mn interact with pre-existing ore due to temperature, fluid pressure, physico-chemical property of fluid gradient. Structurally, faulting and folding contribute to the movement of elements as one end of the system gets depleted the other end of the system gets enriched and vice versa. To better understand this metasomatic activity, it is crucial to conduct mass balance studies of these elements. Grant (1986) introduced the isocon diagram which is a modification of Gresen's equation (1967) to ascertain which elements are directly or indirectly related to alteration through enrichment and depletion of Ca, Mg, Si, Fe, C and Mn. As the section approaches from altered to less altered manganese ore the mineral chemistry gradually changes from a manganese rich matrix composed of manganomelane and todorokite to a carbonate rich matrix composed of braunite, dolomite, kutnohorite and Mn-rich calcites.
Keywords: Metasomatism (Mineralogy); Manganese ores -- Geology -- South Africa; Geology -- South Africa; Mamatwan Mine (South Africa)